Efeito da infecção pelo vírus da febre amarela no mecanismo de splicing celular - Ribeiro, Milene Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Yellow fever virus (YFV) causes disease with significant morbidity and mortality in tropical regions. Several viral strategies are avail for recruitment and alteration of the biochemical cellular processes. Cellular splicing mechanisms are essential to diversify the gene expression and increase it’s proteomic potential. Replication of YFV and the interactions between viral and cellular proteins are unknown. The cellular protein hSlu7 has an nuclear localization and an important role in the second catalytic reaction step of the alternative splicing. In our study group demonstrated that under YFV infection hSlu7 translocates to the cytoplasm. The translocation of proteins between nucleus and cytoplasm may represent a viral mechanism of cellular gene expression regulation, interference in the protein availability of the alternative splicing and viral replication control. This study aimed to characterize the interaction between the viral protein hSlu7 and NS5, as well as studying the effects of interactions on the mechanisms of alternative splicing after YFV infection. To identify interaction with YFV NS5 hSlu7 was conducted co-immunoprecipitation assay. To verify changes in cellular splicing replicons were used pEGFP-ADAR, PI12-IL7R, pEFGP-FGFR2 as well as the change of isoforms of XBP-1 endogenous.The results indicated that YFV NS5 protein interacts with hSlu7 and that their interaction may influence cellular metabolism RNA. YFV perform modulation on cellular splicing, the evaluation of replicons suggest that in hSlu7 splicing dependent and independent regulation occurs viral acting on weak splice sites and that the interaction hSlu7-NS5 can change directly or indirectly to regulate trans- acting

O Vírus da Febre amarela (YFV) causa doença com considerável morbidade e mortalidade nas regiões tropicais. Diversos vírus possuem estratégias para a alteração dos processos celulares. Mecanismos de splicing celulares são essenciais para diversificar a expressão dos genes e podem aumentar seu potencial de gerar proteínas. A replicação de YFV e as interações entre proteínas virais e celulares não são totalmente conhecidas. A proteína celular hSlu7 possui sinal de localização nuclear e tem um papel importante nas reações catalíticas do segundo passo do splicing. Estudos demonstram que sob infecção de YFV hSlu7 transloca para o citoplasma. A translocação de proteínas entre o citoplasma e o núcleo pode representar um mecanismo viral da regulação da expressão gênica. Este estudo teve como objetivo a caracterização da interação entre a proteína hSlu7 e NS5 viral, bem como estudar os efeitos de interações sobre os mecanismos de splicing alternativo após a infecção de YFV. Para identificar interação de NS5 de YFV com hSlu7 foi realizado ensaio de co-imunoprecipitação. Para verificar alteração de splicing celular foram utilizados replicons pEGFP-ADAR, pI12-IL7R, pEFGP-FGFR2, bem como a alteração de isoformas de XBP-1 endógenos. Os resultados indicam que NS5 de YFV interage com proteína hSlu7 e que sua interação pode influenciar no metabolismo RNA celular. YFV demonstrou exercer modulação no splicing celular, a avaliação de replicons sugerem que em splicing dependente de hSlu7, bem como a independente ocorre uma regulação viral atuando sobre sítios de splicing fraco e que a interação hSlu7-NS5 pode alterar direta e indiretamente a regulação trans-acting
Keywords: Virologia; Vírus da febre amarela; Flavivírus; Processamento alternativo; Expressão gênica; Interação proteína-proteína; Yellow fever virus